1981
DOI: 10.1002/eji.1830110905
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T cell recognition of Epstein‐Barr virus‐infected B cells. II. Blocking studies with monoclonal antibodies to HLA determinants

Abstract: Monoclonal antibodies specifically binding common determinants on all HLA-A, B anc C antigen molecules blocked the lysis of EB virus-transformed target cells by EB virus-specific cytotoxic T cells reactivated in vitro. Blocking was mediated through binding of the antibodies to the target rather than to the effector cells and was maximal (75 to 85% inhibition of lysis) at saturating antibody concentrations. A similar blocking effect was also shown by a monoclonal antibody binding to beta 2-microglobulin, a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Similar blocking of cytotoxicity by w6/32 has been reported with human cytotoxic cells specific for targets infected with influenza virus or Epstein-Barr virus (28)(29)(30)(31). In these studies, it was suggested that blocking was due to steric hindrance by the mAb, to antibody-induced conformational alteration of the MHC molecule (28,29), or possibly to interference in the association ofthe virus antigen with the MHC molecules (29 (34,35). In the case of Leishmania tropica, these T cells have also been cloned (35).…”
Section: Discussionsupporting
confidence: 80%
“…Similar blocking of cytotoxicity by w6/32 has been reported with human cytotoxic cells specific for targets infected with influenza virus or Epstein-Barr virus (28)(29)(30)(31). In these studies, it was suggested that blocking was due to steric hindrance by the mAb, to antibody-induced conformational alteration of the MHC molecule (28,29), or possibly to interference in the association ofthe virus antigen with the MHC molecules (29 (34,35). In the case of Leishmania tropica, these T cells have also been cloned (35).…”
Section: Discussionsupporting
confidence: 80%
“…Thus, the first regression assays conducted with reconstructed populations of EBV-infected Tdepleted PBMCs as targets and positively selected CD4 ϩ or CD8 ϩ T-cell subpopulations as responders identified CD8 ϩ T cells as the major effectors (7). Furthermore, T cells harvested from regressing PBMC cultures were dominated by CD8 ϩ T-cell effectors that not only killed established LCL targets in a HLA class I-restricted manner (28,50) but also killed EBVinfected B cells early in the process of transformation (29), just as would be required of the T cells mediating regression. However, our data are partly at odds with the more recent work of Nikiforow and colleagues (33), who found that CD8 depletion had no effect on regression, whereas CD4 depletion appeared to completely abrogate the response.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally infected cultures of PBMCs from EBV-immune (seropositive) donors show early B-cell proliferation but then a regression of B-cell outgrowth that coincides with the reactivation of a memory T-cell response; EBV nonimmune (seronegative) donor cultures show continued B-cell growth irrespective of the presence of autologous T cells. Much of the early literature using this system indicated that regression was associated with the appearance of EBV latent antigen-specific T cells that were operationally HLA class I-restricted in cytotoxicity assays on LCL targets (28,29,38,50) and were therefore assumed to be CD8 ϩ T cells. Indeed, the first experiments separating CD4 ϩ and CD8 ϩ T cells from PBMC cultures strongly supported this assumption (7).…”
mentioning
confidence: 99%
“…To confirm that these T, cells were MHC class I restricted in their lysis of HCMV-infected cells, the cytotoxicity of effector cells from individual wells was assayed against HCMVinfected autologous target cells in the presence and absence of W6132, an anti-HLA class I monoclonal antibody, which inhibits cytotoxicity mediated by MHC class I-specific T, cells [25]. Specific lysis of autologous HCMV-infected fibroblasts was inhibited at a 11250 dilution, providing confirmatory evidence of the MHC class I restriction of these effector cells (Fig.…”
Section: ) Grown In the Presence Of 24-h Hcmv-infected Cells And Molmentioning
confidence: 99%
“…Each well was assessed for lectin-dependent cytotoxicity to detect the presence of cytotoxic lymphocytes irrespective of their specificity [ 151, and against autologous HCMV-infected target cells. HCMVinfected cells were also more susceptible to natural killer lysis [29], therefore, both the virus specificity, using autologous fibroblasts infected with either VZV or HSV, and MHC restriction, using HLA-mismatched HCMV-infected cells or autologous HCMV-infected cells in the presence of W6132 [25], of the effector cells was examined. The number of wells mediating virus nonspecific or non-MHC-restricted lysis varied from assay to assay, even in the same subject; no non-MHC-restricted but HCMV-specific T, cells were identified in these experiments [30].…”
Section: Relative Frequency Of Hcmv-specific Tp For Different Stagesmentioning
confidence: 99%